2015
DOI: 10.1159/000431230
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Associated Hyperparathyroidism: A Pooled Analysis

Abstract: Background: Lithium treatment has been associated with hyperparathyroidism (HPT). However, there are conflicting data regarding the rate of single- (SGD) versus multiple-gland disease (MGD) as well as the optimum surgical approach in these cases. Methods: Published data were identified through systematic electronic literature searches. Studies that fulfilled the preset inclusion criteria were analyzed (n = 12). Results: These studies documented 210 lithium-associated HPT (LAH) cases. Of these, 103 (49%) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Several studies stated that patients with carcinoma were older than those with a benign disease (28,29,31). Similary, we reported that patients with >45 age were statistically significant have a malignant lesion than those with <45 age, which is also independent risk factor for malignancy by 4.2 times by regression analys.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies stated that patients with carcinoma were older than those with a benign disease (28,29,31). Similary, we reported that patients with >45 age were statistically significant have a malignant lesion than those with <45 age, which is also independent risk factor for malignancy by 4.2 times by regression analys.…”
Section: Discussionsupporting
confidence: 83%
“…Most studies have shown that lithium-induced hyperparathyroidism is associated with the presence of a solitary parathyroid adenoma (9296). However, lithium-induced polyglandular hyperplasia has also been described (9597).…”
Section: Lithium and Parathyroid Tumorsmentioning
confidence: 99%
“…If a patient's medical team has recommended surgery, imaging assistance for surgical planning may be equivocal. Given the high rate of multiglandular parathyroid disease (MGD) (20–55%) [8, 9, 10, 11, 12, 13], it is important to note that the normally high sensitivity of sestamibi imaging in detecting parathyroid adenomas goes down with concomitant thyroid abnormalities and in MGD patients [17, 23, 24]. According to Nichols et al [25, 26], sestamibi imaging sensitivity is 61% for MGD versus 97% for single-gland parathyroid disease (SGD).…”
Section: Review Of the Literature: Medical Versus Surgical Managementmentioning
confidence: 99%
“…Care needs to be employed in utilizing the surgical approach, due to the heterogeneous types of lesions noted in LAH. Estimates for prevalence of MGD range from 20% up to 55% in different series [9, 10]. It has also been noted in studies that patients with SGD tend to be easier to control and to remain normocalcemic after parathyroidectomy.…”
Section: Review Of the Literature: Medical Versus Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation